PENGEMBANGAN APLIKASI BANK SAMPAH BERBASIS WEBSITE (STUDI KASUS: KSM BIMA KELURAHAN TELUK PURWOKERTO SELATAN) - Dwi Krisbiantoro; Abdul Azis; Siti Rofiah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
The Garbage Bank KSM BIMA is one of the Garbage Banks located in the Kelurahan of Teluk, Subdistrict of South Purwokerto, which operates independently in the field of waste management. The current management of the waste bank is still done manually, so that officers experience difficulties including when a member who is saving money is constrained by the price of waste, which sometimes changes the price of waste, which makes officers have to carefully look at the current garbage price table. The next obstacle is that by reporting the recorded savings results, there are sometimes differences in balances with the waste bank manager and difficulties in making a report on the amount of waste per category and a report on the state of cash. This study aims to develop a garbage bank application in order to facilitate officers in managing the garbage bank data, as well as improve the quality of service to customers and partners of waste. This application was developed with the PHP programming language and Codeigniter Framework, while the system development method used in making applications is to use the waterfall method. Validation of functionality testing using the blackbox testing method and 100% valid test results from 30 test cases provide results in accordance with the test plan and find no errors in running the application functions.